Clinical and clinicopathological features and outcomes of cats with suspected dietary induced pancytopenia. (7th January 2023) - Glanemann, Barbara; Humm, Karen; Abreu, Mariana; Aspinall, Sophie; Buckeridge, David; Carveth, Hope; Darcy, Hannah; Florey, Jessica; Frowde, Polly; Gajanayake, Isuru; Green, Kate; Holmes, Emma; et al.
Abstract: Background: After a strong epidemiological link to diet was established in an outbreak of pancytopenia in cats in spring 2021 in the United Kingdom, 3 dry diets were recalled. Concentrations of the hemato‐ and myelotoxic mycotoxins T‐2, HT‐2 and diacetoxyscirpenol (DAS) greater than the European Commission guidance for dry cat foods were detected in the recalled diets. Objectives: To describe clinical and clinicopathological findings in cats diagnosed with suspected diet induced pancytopenia. Animals: Fifty cats presenting with pancytopenia after exposure to a recalled diet. Methods: Multicenter retrospective case series study. Cats with known exposure to 1 of the recalled diets were included if presented with bi‐ or pancytopenia and underwent bone marrow examination. Results: Case fatality rate was 78%. Bone marrow aspirates and biopsy examination results were available in 23 cats; 19 cats had a bone marrow aspirate, and 8 cats had a biopsy core, available for examination. Bone marrow hypo to aplasia—often affecting all cell lines—was the main feature in all 31 available core specimens. A disproportionately pronounced effect on myeloid and megakaryocytic cells was observed in 19 cats. Myelofibrosis or bone marrow necrosis was not a feature. Conclusion and Clinical Importance: Mycotoxin induced pancytopenia should be considered as differential diagnosis in otherwise healthy cats presenting with bi‐ or pancytopenia and bone marrow hypo‐ to aplasia.